1982
DOI: 10.1007/bf00381663
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic aspects in operated ankle fractures

Abstract: A long-term follow-up (3.5 years mean) of 106 operated ankle fractures out of 167 patients revealed 73.7% excellent and good, 16% acceptable and 10.3% poor results. Anatomically exact reduction was shown to be a prerequisite for good results and was seen in 77.2% of all cases. By neglecting biomechanical principles an insufficient reconstruction led to a poor final outcome. But even in 11% of the excellent operatively treated fractures late arthrosis developed. Statistical analysis showed that the onset of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 7 publications
3
19
0
4
Order By: Relevance
“…Other authors have reported similar findings. 4,6,13,27 The predictive value of other variables is not clear. Kennedy et al 13 found that an age of greater than 57 years predicted a poorer outcome after ankle fracture than an age of 57 years or less.…”
Section: Broos and Bisschopmentioning
confidence: 99%
See 4 more Smart Citations
“…Other authors have reported similar findings. 4,6,13,27 The predictive value of other variables is not clear. Kennedy et al 13 found that an age of greater than 57 years predicted a poorer outcome after ankle fracture than an age of 57 years or less.…”
Section: Broos and Bisschopmentioning
confidence: 99%
“…2,6,18,20,27 While no single outcome measure is uniformly used after ankle fracture, a combination of functional outcome questionnaires, subjective rating of recovery by the patient, and objective measures of impairment appears appropriate.…”
mentioning
confidence: 99%
See 3 more Smart Citations